[Haskell-cafe] ((a -> b) -> c) -> (a -> m b) -> m c
lemming at henning-thielemann.de
Sun Sep 9 06:12:11 EDT 2007
On Sun, 9 Sep 2007, Stuart Cook wrote:
> (Inspired by this reddit thread.)
> When combining monadic and non-monadic code, I've often wished for a
> magical combinator of type
> (Monad m) => ((a -> b) -> c) -> (a -> m b) -> m c
> which would let me inject a monadic function into a pure one, then
> wrap the ultimate result to ensure that no nastiness escapes.
If the signature would be
(Monad m) => ((a -> b) -> c) -> m (a -> b) -> m c
it would be possible, and the implementation would be 'liftM'/'fmap'.
In the Reader monad you can even convert
(a -> m b) to m (a -> b)
More information about the Haskell-Cafe